The Impact of Collaborative Reading Activities on Students' Reading Comprehension in Hortatory Texts - Rajagukguk, Windy sb; Sinaga, Nenni Triana; Pakpahan, Carolina (Lembaga Riset dan Inovasi Almatani, 2025)
This study investigates the impact of collaborative reading activities on students’ reading comprehension in hortatory texts. The research was conducted using a quantitative approach with a pre-experimental design involving one group of students. The data were collected through a pre-test, and a post-test of 20 multiple-choice questions focused on hortatory texts. The treatment was done through collaborative reading activities, where students worked in groups to read, discuss, and analyze the given texts. After the treatment, the results revealed a significant improvement in students’ reading comprehension. The mean score increased from the pre-test to the post-test, reaching an average of 82.35. Furthermore, the result of the t-test calculation showed that the obtained t-value (8.855) was higher than the t-table value (1.740) at a significance level of 0.05, indicating a statistically significant difference. These findings suggest collaborative reading activities effectively enhance student's understanding of hortatory texts. The study recommends using collaborative strategies in reading classes to foster deeper comprehension and critical thinking.